Family Socioeconomic Status and Adolescent School Satisfaction: Does Schoolwork Support Affect This Association? - Horanicova, Simona; Husarova, Daniela; Madarasova Geckova, Andrea; de Winter, Andrea F.; Reijneveld, Sijmen A. (Frontiers in Psychology, 2022)
Background: Socioeconomic disadvantages have previously been associated with adolescents’ attitudes towards school and access to education; however, role of possible moderators that may prevent the undesirable consequences is mostly unknown. Therefore, the aim of this study is to explore the association of family socioeconomic status (SES) and internal and external schoolwork support with adolescents’ school satisfaction and whether schoolwork support modifies these associations. Methods: Data come from the cross-sectional Health Behaviour in School-aged Children study collected in 2018 from Slovak 15-year-olds (N=1127; 52.7% boys). Socioeconomic status was measured by Family Affluence Scale (low; middle; high). School satisfaction was measured via school engagement and attitudes towards education. Schoolwork support was measured regarding two groups of sources inside and outside the family, separately. Logistic regression models were used to explore the associations of SES and schoolwork support with school satisfaction as well as the moderating effect of schoolwork support. Results: Adolescents with low SES were more likely to feel indifferent towards school and education (odds ratios/95%-confidence interval: 1.77/1.26-2.49), and similarly, adolescents who did not have schoolwork support inside or outside the family (1.38/1.02-1.87, and 1.50/1.01-2.22, respectively). Schoolwork support moderated these associations. Adolescents with low and middle SES without support inside or outside the family were more likely to feel indifferent than satisfied (2.72/1.21-6.10; 3.00/1.27-7.06; and 2.86/1.05-7.80; 6.04/1.72-21.24 respectively). Conclusion: Adolescents from low and middle SES without schoolwork support inside or outside the family are more likely to feel indifferent towards school and education.